The Moral Values of Serat Wulangreh as a Foundation for Character Education among Adolescents in the Fishing Village of Bandengan - Suprihatiningsih, Suprihatiningsih; Astuti, Tri Marhaeni Pudji; Priyanto, Agustinus Sugeng; Sunarto, Sunarto (Proceedings of International Conference on Science, Education, and Technology, 2025)
The purpose of this study is to explore the moral values in Serat Wulangreh by Sri Susuhunan Pakubuwana IV and analyze its relevance as a moral foundation in character education for adolescents in Kampung Nelayan Bandengan. This research focuses on the phenomenon of deviant behavior among adolescents which indicates the weakness of internalizing character values that are contextual with the local culture. The methode used in this study is a qualitative case study approach, which combines in-depth interviews, participatory observation, focused group discussions (FGD), and analysis of the Serat Wulangreh tembang texts. The findings of the study show that Serat Wulangreh contains moral values such as diligence, discipline, humility (tawadhu’), self-control, moral vigilance, and honesty, which align with the character framework according to Lickona. These values play a crucial role in shaping adolescent behavior with a strong Javanese moral foundation. The conclusion of this study is that the integration of values from Serat Wulangreh into community-based character education can strengthen the moral foundation of adolescents in behaving well.